Asuhan Kebidanan Berkelanjutan (Continuity of Care) pada Ny. R Umur 35 Tahun G3P2A0 - Leni Andriyani; Maftuchah (Jurnal Kesehatan Ilmiah Aufa Royhan, 2025)
Abstract Continuous midwifery care, or continuity of care, is a comprehensive midwifery care from pregnancy, childbirth, postpartum, Newborn, family planning provided by midwives to monitor maternal and infant health and can help the government in reducing maternal and infant mortality rates in Indonesia, because with the existence of continuous midwifery care, or continuity of care, in addition to preventing complications. This care involves providing comprehensive care to provide comfort, increase maternal satisfaction, reduce unnecessary interventions. The purpose of this study was to provide continuous care to Mrs. R, 35 years old, G3P2A0, at the Bangetayu Community Health Center in Semarang. The research design used was descriptive and case study. The results showed that Mrs. R, 35 years old, G3P2A0, was physiologically pregnant. The labor process took place normally at 40 weeks of gestation, accompanied by monitoring of the postpartum period and the condition of the newborn that went well and without complications.